2002
DOI: 10.1080/028443102753478363
|View full text |Cite
|
Sign up to set email alerts
|

Patient-rating of long term results of silicone implant arthroplasty of the scaphoid

Abstract: Thirty-two patients had silicone implant arthroplasty of the scaphoid in our unit between 1974-1988. Ten years later eight had had their implants removed because they had failed. Twenty-four of the 32 were reviewed at an intermediate clinical follow up examination between 1988-89 and 21 by patient rated wrist evaluation 10 years later. Grip strength compared to the non-injured hand varied between 38% and 136% (mean (SD) 78 (25)%). Nine of the 24 wrists showed no signs of bone cysts, while 15 had intraosseous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The treatment reported in the literature for failed partial carpal arthrodesis, carpal silicone implant, first-row resection, or advanced Kienböck disease surgery is usually TWF. [24][25][26][27][28][29] TWF results are not always satisfactory. 30,31 This procedure has complications and the results on pain and function, especially in patients with multiple surgeries are sometimes disappointing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment reported in the literature for failed partial carpal arthrodesis, carpal silicone implant, first-row resection, or advanced Kienböck disease surgery is usually TWF. [24][25][26][27][28][29] TWF results are not always satisfactory. 30,31 This procedure has complications and the results on pain and function, especially in patients with multiple surgeries are sometimes disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…Kaarela et al observed a 41% rate of this type of complication with lunate implants at 5.6 years follow-up. 37 Vinnars et al had a 62% rate at 10 years follow-up for scaphoid implants 29 and Minami et al had a 33% rate at 15.3 years follow-up with trapezial implants. 38 Wrist arthrodesis is a salvage solution in cases of progressive symptomatic degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Silicone prosthesis for the proximal pole was proposed by Swanson. The long-term results 20,28 are satisfactory in terms of pain control and function; however, the rate of revision surgery for secondary dislocation of the implant is relatively large, in addition to a high rate of cystic bone changes secondary to a synovitis caused by the silicone implant. 29 Furthermore, this implant does not prevent the evolution of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…A simple resection of the proximal pole of the scaphoid could be performed, but there is a concern regarding the stability of the carpus. 20 Many different surgical reconstructive options for SNAC wrist have been reported. Several papers have reported using a synthetic replacement such as silicone, Vitallium, 21 acrylic 22,23 and titanium, 24 glutaraldehyde and bovine fibrocartilage, 25 and collagen and bone morphogenetic protein (BMP).…”
Section: Surgical Treatment Options For Scaphoid Nonunionmentioning
confidence: 99%